Sulphur dioxide removal using dried eggshell - Hoo, Sie Kei (2018)
Due to the global industrialization, the emission of sulfur dioxide gas becomes a concern nowadays. SO2 has adverse effects to the environment as it tends to react with water to form acid rain. The interests of turning eggshell waste to products had been growing in different sectors. However, only a few research had been done using eggshell waste for gas removal. In this study, eggshell-based adsorbents (with membrane and without membrane) were prepared without undergoing any modifications. The adsorption test using eggshell-based adsorbents were carried out at three different parameters, where the influence of particle size, reactor temperature and relative humidity were studied and evaluated. Owning to the presence of a network of fibrous protein offers large surface area to eggshell with membrane (ESM), it showed better adsorption capacity than the eggshell without membrane (ES). Besides, comparison had been done between commercial calcium carbonate (CCC) and ESM, where the results showed CCC had higher SO2 removal capacity, where the purity grade of CCC, which is approximately 99% was believed as one of the main reason to have better adsorption performance. At the presence of 40% relative humidity, significant breakthrough time had observed in ESM and CCC, where the adsorption capacity were 18.7472 SO2 mg/g and 23.2435 SO2 mg/g. The adsorbed water to the adsorbents enhanced the ion mobility, permit SO2 hydrolysis reaction to produce H2SO3. Characterizations of the eggshell-based adsorbents had been evaluated by FTIR, SEM and EDS analysis.